BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Sesame diseases-An annotated bibliography from the 1900-1988 literature. Compiler, G. S. Saharan, Department of Plant Pathology, Haryana Agricultural University, Hissar 125 004, India, IRDC-MR 227 e.India is a major oilseed producing country but its total annual production of oilseeds is far short of dietary demands of its population. India has also the unique distinction ofÂ having the highest acreage under sesame in the world and out of the nine oil seed crops that are grown in this country, sesame is the third major source of edible oil after groundnut and rapeseed-mustard. Like all other oilseed crops, the productivity of sesame is also very low in India.